Cold therapy for the management of pain associated with deep breathing and coughing post cardiac surgery - Chailler, Myrianne (University of Ottawa (Canada), 2009)
Incisional, chest and sternal pain is prevalent in patients after cardiac surgery. If pain is not properly managed it may prevent patients from performing activities such as deep breathing and coughing (DB & C) which are important for preventing postoperative respiratory complications. There is a scarcity of research about the nonpharmacologic modalities for treating post cardiac incisional and sternal pain. Of these modalities, cold therapy is a strategy that has been used effectively over many decades in a number of areas including orthopedic surgery. The beneficial effects of cold therapy for pain management have been widely documented and the side effects are minimal, yet its use is limited in post-surgical cardiac patients. Nurses can have an active role in relieving patients' surgical pain with cold therapy. Presently, there are no studies in the literature that specifically address cold therapy for sternotomy pain management following coronary artery bypass graft (CABG) surgery. The objectives of this study were: (1) to evaluate the effects of cold therapy on pain associated with DB & C post cardiac surgery; (2) to identify sensations from the patients' perspective when cold in the form of a gel pack is applied to the median sternotomy chest incision before DB & C; (3) to identify patients' preferences for gel or no gel pack application. A crossover research design was utilized and each patient served as their own control. Participants underwent four sessions of DB & C every two hours on postoperative day two. Two sessions were preceded by cold application and two sessions were without cold application. At the end of the four sessions of DB & C, patients were asked about their preferences for gel or no gel pack application. Pain scores associated with DB & C were significantly decreased with the application of cold therapy (F=28.69, p<.001). Most participants preferred using the gel pack before performing the DB & C exercises (n=22; 69%) and there were 2 (6%) participants who preferred DB & C without the gel pack, the other participants (n=8) had no preference. The sensations experienced were similar among all participants, most described coolness (n=9; 28%) or cold (n=23, 72%). In conclusion, this study demonstrates that cold therapy is useful for managing patients' pain associated with DB & C following CABO surgery. Cold therapy is low risk, low cost and can be easily integrated into nursing practice since cold packs are easily accessible in most hospitals. With nurses' initial supervision, cold therapy is a safe and effective pain management modality that gives patients an active role in pain management. Further research is recommended on the application of other cold modalities such as the use of ice chips as the cold source before DB & C as well as performing the intervention earlier after the surgery on postoperative day one.
Keywords: Health Sciences, Medicine and Surgery.; Health Sciences, Nursing.